Pengaruh Citra Merek, Kepercayaan Merek, Dan Pengalaman Merek Dalam Proses Membangun Merek Sepatu Lokal - Aulia Mauliddinia (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
The fashion industry, particularly in the rapidly evolving and changing footwear industry, it is important for companies to understand consumer perceptions of brands in order to build and maintain a company’s image. This research aims to understand how Gen Z consumers in DKI Jakarta evaluate brands and react to branding practices by involving brand management constructs, namely brand image, brand trust, brand experience, wich lead to consumer purchase intention. A quantitative research design was employed using the Structural Equation Model (SEM) method, and data analysis employing statistical software. Data collection was done through online questionnaires to 100 respondents. The result of this study demonstrate that brand experience influences brand image, brand experience influences brang trust, brand image influences brand trust, brand image influen ces purchase intention, and brand trust influences purchase intention.